Impacts of building defects on the health and wellbeing of apartment residents: a scoping review - Andrews, Fiona; Sal Moslehian, Anahita; Johnston, Nicole; Tucker, Richard (Building research and information : the international journal of research, development and demonstration, 2024)
While recent high-profile incidents have highlighted the impacts of building defects, there remains a dearth of comprehensive research that examines the full spectrum of health risks encountered by residents living in apartments affected by these defects. In this paper, an interdisciplinary perspective provides a comprehensive and structured synthesis of the literature on the varied impacts of lifecycle construction quality characteristics and defects on the health and wellbeing of apartment residents, including classification of methodological approaches. Twenty-seven peer reviewed articles published from 2010 onwards were selected and analysed through a systematic process from eight major online databases. Our findings synthesize the impacts of construction defects on three aspects of health: (1) physical health; (2) mental health; and (3) the general wellbeing of occupants. For each aspect, we also identify the associated defects. This paper highlights significant knowledge gaps in relation to methodologies, cohorts sampled, and the wider health impacts of certain defects. In relation to policy and practice, we discuss the need for a broader, interdisciplinary understanding of the extent of apartment building construction issues, and thus for a more holistic exploration of the impacts on health of these issues.